Gambaran Pengetahuan Mahasiswa STIKES Wira Husada Yogyakarta tentang Fungsi Penggunaan Masker di Masa Transisi Endemi Covid-19 - Anggraeni, Dewi Nur; Sugiman, Sugiman; Febriani, Heni; Kristanti, Handriani (Jurnal Sehat Mandiri, 2023)
Masks are self-protection tools used to be free from bacteria, viruses and fungi. During the transitional period of the Covid-19 endemic, there was a notification that masks were no longer an absolute requirement for self-protection. The purpose of this study was to describe the knowledge of students about the function of wearing masks during the transition period of the Covid-19 endemic. The research population consisted of 427 students, and the samples taken were 24 people. This type of research is qualitative and quantitative using cross-sectional descriptive methods, data collection using questionnaires and interviews, qualitative data analysis by creating a new hypothesis regarding the use of masks, and quantitative analysis using univariate methods. The research results obtained were that students had a good category of knowledge 83.33% about the use of masks in the endemic transition, qualitative data analysis for hypothesis testing by confirming the results of interviews, 70% of students had adherence to wearing masks outside or indoors, and then a new hypothesis was developed. The conclusion of this study is that the knowledge of students regarding the use of masks is in the good category, and from the interview results obtained a new hypothesis is made. The suggestion from this study is that it is necessary to carry out further research from the results of the new hypothesis regarding adherence to wearing masks.